Hubungan Body Image Dan Pengetahuan Gizi Seimbang Dengan Status Gizi Remaja Putri Di MA Muhammadiyah Lingadan Tolitoli - Firda Shofia; Choirul Anna Nur Afifah (Lembaga Pengembangan Kinerja Dosen, 2024)
Adolescence is closely related to body image because at this stage adolescents are looking for their identity and identity. Knowledge of balanced nutrition can give adolescents the ability to apply balanced nutrition information to their diet. Abnormal nutritional status in adolescents is generally caused by incorrect nutritional behavior, which is not balanced consumption with nutritional needs. This study aims to analyze the relationship between body image and knowledge of balanced nutrition with the nutritional status of adolescent girls at MA Muhammadiyah Lingadan Tolitoli. This study is a correlational quantitative study with a cross sectional design. Respondents used were all adolescent girls aged 10-18 years at MA Muhammadiyah Lingadan Tolitoli totaling 44 people. Data collection in this study used the MBSRQ-AS Questionnaire (Multidemensional Body Self Relation Questionnaire-Appearance Scale), Balanced Nutrition Knowledge Test and measurement of body weight and height to obtain nutritional status data. Data analysis was performed using the Rank Spearman statistical test. The statistical test results showed that there was no significant relationship between body image and nutritional status of adolescent girls at MA Muhammadiyah Lingadan Tolitoli (p=0.384>0.05) and there was a significant relationship between balanced nutrition knowledge and nutritional status of adolescent girls at MA Muhammadiyah Lingadan Tolitoli (p=0.004<0.05).